Arctic tale - Evans, Kattie; Miller, Chris, 1975-; Leipzig, Adam; Smart, Keenan; Woolverton, Linda; Richards, Mose; Gore, Kristin, 1977-; Ravetch, Adam; Robertson, Sarah; Queen Latifah, 1970-; Paramount Classics (Firm); National Geographic Films; et al. (Hollywood, California Paramount Pictures, 2007)
Filmed over the span of fifteen years, Arctic tale follows a polar bear cub and a walrus pup as they learn to survive in the wild and face increasing challenges posed by global warming.
Special features: Making of Arctic tale -- "Are we there yet? world adventure : polar bear spotting" -- Theatrical trailer -- Previews.
Documentary.
Title from disc surface.
Special features: Making of Arctic tale, "Are we there yet? World adventure : polar bear spotting."
Music, Joby Talbot.
Narrator, Queen Latifah.
MPAA rating: G (general audiences).
Keywords: Zoology -- Arctic regions; Polar bear -- Arctic regions; Walrus -- Arctic regions; Animals -- Infancy -- Arctic regions; Global warming -- Arctic regions; Documentary videos; Television programs; Documentary television programs; Television programs for the hearing impaired; Documentary films